Collective construction of dimensions that support the design of open educational resources in the teaching of mathematics - Lara Sáenz, Noemí Gabriela; Ordaz Guzmán, Teresa; Montero Vargas, René (IE Revista de Investigación Educativa de la REDIECH, 2025)
This article presents the findings of qualitative research that aims to propose central dimensions for the design of open educational resources to improve the learning of mathematics in high school. The study sample was made up of 30 women, between 16 and 17 years old, students at a public high school, in the urban area of the State of Querétaro, Mexico. Their voices, experiences, emotions, beliefs, and patterns of their learning processes in mathematics were collected through two instruments: life history and a questionnaire. The information obtained was transcribed and categorized for analysis. The results showed six dimensions to consider in the design process of open educational resources that revolve mainly around the use of technologies in training processes, and the evaluation of mathematics learning. These findings open the possibility of designing educational resources based on disciplinary needs in conjunction with the students’ voices.